PENGARUH PEMBELAJARAN TEAM GAMES TOURNAMENT TERHADAP KECERDASAN EMOSIONAL SISWA - Ratih Handayani (Eksponen, 2017)
This quasi experiment research was aimed to find outthe influence of interaction between cooperative learning of TGT and gender on the seventh grade of SMPN 4 Kotabumi students’ emotional intelligence. The research population was all of the seventh grade of SMPN 4 Kotabumi students in academic year 2016/2017 consisting of 163 students with the research sample of VIIA class as the experimental class taught by cooperative learning of TGT and VIIB class as the control class taught by using direct teaching and learning model. Meanwhile, the instruments used were questionnaire was used to collect the data of students’ emotional intelligence. The data analysis was done by t-test with the help of SPSS 20 after it was found that the data were normal and homogenous through normality and homogeneity test. Based on the research result, some conclusions were made as follows there is interaction influence between cooperative learning of TGT and gender on the seventh grade of SMPN4 Kotabumi students’ emotional intelligence.